De Novo Mutation of m.3243A>G together with m.16093T>C Associated with Atypical Clinical Features in a Pedigree with MIDD Syndrome. (4th April 2019) - Jiang, Zhixin; Zhang, Yinan; Yan, Jingbin; Li, Fengwen; Geng, Xinqian; Lu, Huijuan; Wei, Xiaoer; Feng, Yanmei; Wang, Congrong; Jia, Weiping
Abstract : Background . The syndrome of maternally inherited diabetes and deafness (MIDD) is typically caused by the m.3243A>G mutation and widely considered maternally inherited. In our study, we aimed to investigate the heredity way of the m.3243A>G among pedigrees with MIDD and discover novel mitochondrial DNA mutations related to atypical clinical phenotypes. Methods . Heteroplasmy levels of the m.3243A>G mutation in peripheral blood, saliva, and urine sediment of 31 individuals from 10 unrelated pedigrees were measured by pyrosequencing. Clinical evaluations including endocrinological, audiological, and magnetic resonance imaging (MRI) examinations, mitochondrial function evaluation in peripheral blood mononuclear cells (PBMCs), and whole mitochondrial DNA (mtDNA) sequencing were performed among the spontaneous mutant pedigrees. Results . Among the 10 unrelated MIDD pedigrees, we found that the de novo m.3243A>G mutation occurred in the family 1957 (F1957). The proband (F1957-II-1) and her son (F1957-III-1) both manifested diabetes with mild bilateral sensorineural hearing loss (SNHL) and abnormal brain MRI, and F1957-III-1 also complained of severe nausea and vomiting. Mitochondrial function evaluation in PBMCs revealed an increased level of ROS generation and decreased levels of ATP and mitochondrial membrane potential (ΔΨm) in the two m.3243A>G carriers. Whole mtDNA sequencing also revealed a de novo heteroplasmic substitution at m.16093T>C in both the proband and her son. Conclusions . Our study showed that de novo m.3243A>G mutation accompanied by other point mutations may occur in the very early embryonic or germ cell stage without maternal inheritance, bringing about both typical and atypical clinical features.